Water Quality of Situ Cibanten Based on Shannon-Weaver Diversity Index Value - Saifullah Saifullah (Jurnal Perikanan dan Kelautan, 2015)
Situ Cibanten used by local communities especially for bathing and washing. These waters get pressures by anthropogenic disturbances. Objective of the study is to evaluate water quality of Situ Cibanten based on their plankton diversity. The study conducted from April – July 2014 at Situ Cibanten, district Ciomas, Serang Regency. Plankton sample taken using plankton net no.25 (mesh 55 – 60 µm) and observed at Aquaculture Laboratory, Faculty of Agriculture, Sultan Ageng Tirtayasa University, Banten Province. The research use purpossive sampling methods to determine the sampling stations. Plankton diversity calculated using Shannon Weaver diversity index. The results showed plankton diversity index value at Situ Cibanten range from 0.57 – 1.09, which is classified low diversity index and fall into the category heavy polluted.